Syntheses of Clofarabine and Related C2′-β-fluorinated Nucleoside Analogues - Grigorii, Sivets; Aleksey, Sivets (Journal of New Developments in Chemistry, 2022)
A multistep synthesis of 2-chloro-9-(2′-deoxy-2′-fluoro-β-D-arabinofuranosyl) adenine (clofarabine) is described from methyl β-D-ribofuranoside. A new improved method for preparation of 1,2-diacetyl D-ribofuranose derivative was developed via acetolysis of tri-O-pivaloylated D-ribofuranoside and plausible mechanism of the reaction was proposed. Synthesis of 3′,5′-di-O-pivaloyl-2,6-dichloropurine β-D-riboside along with isomeric 2′,5′-di-O-pivaloyl nucleoside was carried out by stereoselective glycosylation reaction of 2,6-dichloropurine with peracylated D-ribofuranose followed by regioselective 2´-O-deacetylation of protected β-ribonucleoside with different bases. Mild C2′-β-fluorination of the purine 3′,5′-di-O-pivaloyl ribonucleoside with an excess of diethylaminosulfur trifluoride afforded protected 2,6-dichloropurine 2′-fluoro β-D-arabinoside as the key intermediate. Efficient route to clofarabine was also investigated using anion glycosylation of 2-chloroadenine potassium salt with the 1-α-bromide and potassium tert-butoxide in binary solvent mixture, chromatography for separation of a mixture of anomeric nucleosides (a β/α ratio of 3.0:1) and deacylation of benzoylated 2′-fluoro β-nucleoside. Novel N6-isopentyl clofarabine analogue was synthesized by a direct alkylation of the parent nucleoside
Keywords: Anticancer purine nucleoside; selectively protected D-ribofuranose derivatives; glycosyl bromide; stereoselective glycosylation; fluorination